Gambaran Kemandirian Belajar Siswa SMP N 1 Bayang - Purmia, Qori; Zikra, Zikra (Lembaga Yasin AlSys, 2024)
This research was motivated by the large number of students who did not do their assignments, did not bring textbooks, this was caused by the low level of student learning independence. This research aims to describe the picture of independent learning of students at SMP N 1 Bayang. This research uses quantitative methods with a descriptive approach. The sample in this study was 131 students at SMP N 1 Bayang who were selected using the starified random sampling technique. Data was obtained using a valid and reliable learning independence questionnaire. The research results show that the learning independence of SMP N 1 Bayang students is generally in the medium category (66.47).